Numerical determination of free vibration frequencies of a corrugated open cylindrical shell - Grigorenko, A.Ya.; Borysenko, M.Yu.; Boychuk, O.V.; Sperkach, S.О.; Bezuglaya, А.D. (Reports of the National Academy of Sciences of Ukraine, 2023)
In the work, the frequencies and forms of free vibrations of thin corrugated open cylindrical shells with free and rigidly fixed one and two ends were determined using the finite element method. A comparison of the obtained results with the results for an open shell with another opening angle and a closed shell with the same geometric and physic-mechanical parameters, as well as boundary conditions, was carried out. The approaches implemented in work make it possible to study the dynamic characteristics of corrugated shells of other configurations and can be used to evaluate the accuracy of other approaches.